2020
DOI: 10.1001/jamanetworkopen.2020.30207
|View full text |Cite
|
Sign up to set email alerts
|

Association of Improved Periconception Hemoglobin A1c With Pregnancy Outcomes in Women With Diabetes

Abstract: IMPORTANCE Prepregnancy diabetes is associated with higher perinatal and maternal morbidity, especially if periconception glycemic control is suboptimal. It is not known whether improved glycemic control from preconception to early pregnancy and midpregnancy periods can reduce the risk of adverse perinatal and maternal outcomes. OBJECTIVE To determine whether a net decline in glycated hemoglobin A 1c (HbA 1c ) from preconception to the first half of pregnancy is associated with a lower risk of adverse outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…24 In a recent study using population-based data from Canada using an analytical approach similar to the current analysis, Davidson et al demonstrated that every incremental decrease in HbA 1c by 6 mmol/mol (0.5%) during pregnancy was associated with a reduced risk of congenital anomalies and preterm birth, as well as maternal outcomes including severe maternal morbidity, preeclampsia, and death. 20,32 Prior studies have also documented an association between an early pregnancy or periconceptional HbA 1c and increased risk of fetal and infant death. 6 Taken together these findings suggest that repeated HbA 1c assessments can be clinically valuable data points for both clinical management and risk stratification.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…24 In a recent study using population-based data from Canada using an analytical approach similar to the current analysis, Davidson et al demonstrated that every incremental decrease in HbA 1c by 6 mmol/mol (0.5%) during pregnancy was associated with a reduced risk of congenital anomalies and preterm birth, as well as maternal outcomes including severe maternal morbidity, preeclampsia, and death. 20,32 Prior studies have also documented an association between an early pregnancy or periconceptional HbA 1c and increased risk of fetal and infant death. 6 Taken together these findings suggest that repeated HbA 1c assessments can be clinically valuable data points for both clinical management and risk stratification.…”
Section: Discussionmentioning
confidence: 99%
“…25 We analysed change in HbA 1c as a continuous measure given validated clinical thresholds for change in HbA 1c have not been defined for pregnancy. As recommended by national guidelines and recent analyses conducted in pregnancy 19,20 we evaluated HbA 1c as an absolute percentage of total haemoglobin using standards set by the International Federation of Clinical Chemistry 26 and with an assay that is currently certified by the US National Glycohaemoglobin Standardization Program with methods and reagents as having documented traceability to the Diabetes Control and Complications Trial Reference Method. 27 The primary outcomes were an LGA infant at birth (>90th percentile birthweight) and neonatal hypoglycaemia.…”
Section: Exposure Outcome and Covariatesmentioning
confidence: 99%
See 2 more Smart Citations
“…For every 1% increase in the HbA1c level, the risk of adverse pregnancy outcomes increases by 3.8 to 7.3%. Davidson et al [ 12 ] found that for every 0.5% decrease in the HbA1c level, the risks of fetal and fetal heart malformations were reduced by 1 and 11%, respectively. In pregnant women with diabetes, maternal hyperglycemia can lead to fetal hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%